Film as Mass Communication and its Responsibility to Social Change - Dhungana, Jivan (Interdisciplinary Journal of Management and Social Sciences, 2024)
This paper considers movies as means of mass communication and attempts to highlight the challenges faced by Nepali movies while communicating with people. It believes that the movies are key artistic presentations by which movie-mediatization is possible and a significant positive change can be brought. Movies are made as effectively to socialize people as to provide entertain to them. It means that the movies are highly responsible for bringing positive vibes in society. In order look at the manner in which films are giving a message to the audience, this paper makes a review of key literature on movie, mass communication, mediatization, and impact of movie on mediatization, analyzes the impact of movies on society, and forwards some key conclusions on epitomizing women as heroes. It also takes into consideration the significant impact made by some Indian movies to the Nepali movie industry, which is not growing well because of the premiere of recent Indian movies that are superior to Nepali movies both in quality and quantity. To conclude, the paper encapsulates the notion of film as an art, which has easily entered into people’s mind and heart, and is changing people’s preoccupied mindset on women and gender roles.